A Study of the Effectiveness of the Use of Cement and Bottom ash Towards the Stability of Clay in Terms of UCT Value. (2017) - Hastuty, Ika Puji; Roesyanto,; Jeriko, B.S.
Abstract: Stabilization is one of efforts in improving the condition of soil which has less good index of properties. One example of stabilization is by adding chemicals into the soil. The chemicals commonly used are cement, lime, and asphalt. This research used the addition of cement and Bottom Ash which was waste material of the combustion of coal that was not used and harmful if disposed carelessly. This research was performed on clay without Bottom Ash mixture, and clay that has been mixed with 1% cement, 2% cement, and Bottom Ash with several percentages of variation levels of mixed materials. This research included preparatory work, laboratory testing, and analysis of the results of laboratory testing. Results that would be achieved is the effect of adding cement and Bottom Ash against Unconfined Compression Test (UCT) value on clay. The results showed that the addition of 2% cement and 9% Bottom Ash with a curing time of 14 days had the largest compressive strength of soil which was 2.69 kg/cm 2 . The addition of 1% cement and 10% Bottom Ash with a curing time of 14 days had the largest compressive strength of soil which was 2.02 kg/cm 2 .The use of 2% cement on clay had a compressive strength of 1.77 kg/cm 2, while the use of 1% cement on clay had a compressive strength of 1.61 kg/cm 2 . It showed an increase in the compressive strength value with the mixture of 2% cement which was 9.62%, compared to compressive strength value with the mixture of 1% cement.